2-Acyl-1-aryl-6, 7-dihydro-1H, 5H-pyrazolo[1, 2-a]pyrazole derivatives: Versatile fluorescent probes with remarkably large Stokes shift. (May 2022) - Petek, Nejc; Erjavec, Bibi; Slapšak, Dejan; Gaber, Aljaž; Grošelj, Uroš; Požgan, Franc; Ričko, Sebastijan; Štefane, Bogdan; Klemenčič, Marina; Svete, Jurij
Abstract: A series of thirteen 2-acyl-6, 7-dihydro-1 H, 5 H -pyrazolo[1, 2- a ]pyrazole derivatives were synthesized by using a copper-catalyzed azomethine-imine-alkyne cycloaddition as a key step. These bimane-related fluorescent compounds with λex = 338–400 nm and λem = 522–644 nm exhibit interesting and promising optical properties, including a remarkably large Stokes shift (150–268 nm), positive solvatochromism, and strong dependence of emission intensity on pH in a range of pH 2–10. The benzotriazolide- and N -succinimidyl ester-functionalized compounds were successfully used as fluorescent probes for protein labelling. Graphical abstract: Image 1 Highlights: Novel electrophilic probes for fluorescence imaging. Facile preparation, broad substrate scope. Typical λex ∼350 nm and λem ∼560 nm. Positive solvatochromism. pH-dependent emission intensity.